Role of Ar-Rahnu as micro-credit instrument in achieving financial self-sufficiency among women micro-entrepreneurs - Nik Azman, Nik Hadiyan; Kassim, Salina; Adewale, Abideen Adeyemi (IIUM Press, 2016)
Compared to conventional pawnbroking, Islamic pawnbroking (or ar-rahnu) is relatively a recent product in the financial market. More recently, however, ar-rahnu-based microcredit facility has grown in importance over the past few years due to the increased awareness on Islamic finance in Malaysia and is increasingly a popular financing option, particularly among women micro-entrepreneurs. This study examines the role of ar-rahnu as a micro-credit instrument among women micro-entrepreneurs and aims to understand how the use of ar-rahnu could help them to achieve financial self-sufficiency. In achieving these objectives, the study conducts a survey on women micro-entrepreneurs in the Siti Khadijah market in Kelantan. Findings of the study are useful for the relevant authorities to take initiatives to promote Islamic-based micro-credit instruments, especially among women micro-entrepreneurs.